Sensory-Specific Appetite Is Affected by Actively Smelled Food Odors and Remains Stable Over Time in Normal-Weight Women. Issue 8 (25th June 2014) - Ramaekers, Mariëlle G.; Boesveldt, Sanne; Gort, Gerrit; Lakemond, Catriona M. M.; van Boekel, Martinus A. J. S.; Luning, Pieternel A.
Abstract: Understanding overconsumption starts with knowledge of how separate factors influence our eating behavior. Food cues such as food odors are known for their effect on general appetite and sensory-specific appetite (SSA). Active sniffing rather than passive exposure may induce satiation over time. The objective of this study was to investigate how actively sniffing banana odors affects general appetite, SSA, and subsequent food intake. In a crossover study, 61 women actively smelled cups containing natural banana, artificial banana odor, or water (no odor) for 10 min. Treatment order was randomly assigned as much as possible. General appetite and SSA were monitored by using 100-mm visual analog scales during the 10 min of active sniffing, followed by ad libitum intake of banana milkshake. Results showed that SSA was consistently high (+12 mm) during actively sniffing natural or artificial banana odors, with no decrease in SSA over time. Sniffing both banana odors increased the appetite for banana (+11 mm) and other sweet products (+4 mm), whereas the appetite for savory products decreased by 7 mm (all P < 0.01) compared with no odor. Actively sniffing banana odor did not significantly influence food intake ( P = 0.68) or general appetite scores ( P = 0.06). In conclusion, SSA scores during active sniffing were identical to the SSA found in a similar study that used passive smelling, suggesting that SSA is independent of the manner of sniffing and exposure time. Moreover, sweet/savory categorization may suggest that food odors communicate information about the nutrient composition of their associated foods. These data clearly show the appetizing effects of food odors.